Influência do desenvolvimento tecnológico sobre o desenvolvimento social a partir das atividades da incubadora tecnológica de Campina Grande, Campina Grande, Paraíba - Torres, Luciana Silva (2003)
This study evaluates the influence of the technological development on the social, beginning from the productive activities developed in the unit agro industrial Recanto 11, in the municipal district of Catolé do Rocha, with the support of the Incubadora Tecnológica de Campina Grande - ITCG, and the Programa de Estudos e Ações do Semi-árido Paraibano of the Universidade Federal de Campina Grande - PEASA/UFCG. The social problems in the semi-arid appeared from hard adverse environmental conditions and they intensified for the lack of appropriate public politics to the education and the development of the area. The problem is expressed by the following inquiry: Which done the influence between the technological development and the social development generate beginning from the productive activity of the Incubadora Tecnológica de Campina Grande, in Campina Grande, Paraíba? The relevance of this work comes from the pretension in collaborating for the study of the relationship among technological and social development, in an attempt of tuming intelligible the education need and technological innovation for the social development, mainly in countries not developed. It also comes from the usefulness for the formulation of public politics and strategies of technological development, identifying actions and performance measures, directed to the diagnosis of the contribution from technological incubators to the well-being of the society. The theoretical referential was composed by the analysis of the function from several social agents' rationalities and your contribution for the social interactions, besides the analysis of the cultural realities from the business society, the State and the technological incubators. The methodology used was composed of some research kinds, descriptive and explanatory research, of field, documental, bibliographical and case study. The uni verse was the people wich compose ITCG and the sample were the director ofthe Incubator, the scientist ofUFCG, the Recanto 11 community leader, the subject of the research get confused with the sample. The collection of data was gave through the literature on the thematic and inserts in the study field. The treatment of data was used of qualitative analysis of the phenomenon. The main limitations of the method consisted of the collection, in the treatment of the data, and in the use of the case study, with possibility of tendentious understanding of the studied phenomenon. The practical referentiai introduces the research results, evaluating them through the comparison with the studied theoretical referential. The results shows ITCG acted articulating the groups and translating each agent's cultural realities on behalf of the development of agro industries communities in situation of social risk, due to the problem of the drought. ITCG acted as social alphabetiers teaching to the social agents the cultural codes of the other groups. The inequalities that existed between the scientist and the country man, deepened by the vexatious report of the man's of the field slavery in the Brazilian northeast, they were minimized by the education given by the own scientist. The University contributed to the reduction of the environmental illiteracy, where the environment was had as the country men's principal rival. The State, when it acts in partnership with the other social agents it gets, to stay as the citizens' principal instrument to control the globalization in function of your values and interests. In ITCG the incubation atmosphere is educational, where the new entrepreneurs are contacted the cultural reality of the undertaker sector, of the State and of other communities of the society, following models merely educational. As conclusion is had that Recanto IfS citizens' path - from slaves to exporters - it was based on two great treasures, the family and the religion. The merit of ITCG was to understand, to respect and to preserve Recanto IIS cultural reality and to motivate the social interaction with other cultural realities capable to generate development in that area. The health, the infantile development, the safety, the house were conquests of Recanto Il. As suggestion is had that the public politics should reproduce environment of development for all the Brazilian citizens in situation of social risk, making the family the base for flowing and harmonicas social interactions among the several social agents.